THE ROLE AND EFFECTIVENESS OF THE STEAM APPROACH IN TEACHING THE TOPIC “TYPES OF CRYSTAL LATTICES” IN CHEMISTRY EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
This study explores the effectiveness of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in teaching the topic “Types of Crystal Lattices” in chemistry classes at general secondary schools. The research utilized interactive methods such as “Wheel of Fortune” and “Lapbook,” as well as the online platform LearningApps.org. Lessons organized based on the STEAM approach were analyzed to assess students’ level of comprehension of the topic. The results of the study confirm the pedagogical significance of applying the STEAM approach in chemistry education.